2022
DOI: 10.1136/neurintsurg-2021-018460
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the eCLIPs bifurcation remodelling system for the treatment of wide necked bifurcation aneurysms: 1 year results from the European eCLIPs Safety, Feasibility, and Efficacy Study (EESIS)

Abstract: BackgroundThe eCLIPs bifurcation remodelling system is a non-circumferential implant that bridges the neck from outside of a bifurcation aneurysm. The goal of the multicenter, post-marketing European eCLIPs Safety, FeasIbility, and Efficacy Study (EESIS), was to present the efficacy and safety results of the eCLIPs device after 365 days of follow-up.MethodsAll patients were to receive an eCLIPs in conjunction with coils. The study was conducted according to good clinical practices and included independent adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The eCLIP device is a hybrid device with both neck bridging and flow-diversion properties ( 98 ). Recent studies have confirmed its effect in assisting coiling aneurysms, such as in de Vries et al’s study ( 99 ) and in Diestro et al’s report ( 100 ). The eCLIP device can be used for the treatment of MCA bifurcation aneurysms; however, it has been less frequently reported.…”
Section: New Devicesmentioning
confidence: 59%
See 1 more Smart Citation
“…The eCLIP device is a hybrid device with both neck bridging and flow-diversion properties ( 98 ). Recent studies have confirmed its effect in assisting coiling aneurysms, such as in de Vries et al’s study ( 99 ) and in Diestro et al’s report ( 100 ). The eCLIP device can be used for the treatment of MCA bifurcation aneurysms; however, it has been less frequently reported.…”
Section: New Devicesmentioning
confidence: 59%
“…The eCLIP device is a hybrid device with both neck bridging and flow-diversion properties (98). Recent studies have confirmed its effect in assisting coiling aneurysms, such as in de Vries et al 's study (99) and in Diestro et al 's report (100).…”
Section: Barrel and Eclip Devicesmentioning
confidence: 94%
“…In recent studies, complete occlusion and adequate obliteration were archived in 62%–67% and 85%–89%, respectively, during the follow-up period. 47 , 48) The technical success rate of deployment of the eCLIPs was 90%–96%. Procedure-related complications included subarachnoid hemorrhage due to guidewire perforation of the daughter branch, asymptomatic thrombotic events, and vasospasm or dissection due to an eCLIPs microcatheter.…”
Section: Other Stenting Techniquesmentioning
confidence: 99%
“…The proximal Then, the guidewire is advanced intothecontralateralbranchartery.Theribsoftheleaflet segmentallowaccessforthemicrocathetertotheaneurysmalsacforcoiling.Inrecentstudies,completeocclusion andadequateobliterationwerearchivedin62%-67%and 85%-89%,respectively,duringthefollow-upperiod. 47,48) The technical success rate of deployment of the eCLIPs was90%-96%.Procedure-relatedcomplicationsincluded subarachnoidhemorrhageduetoguidewireperforationof the daughter branch, asymptomatic thrombotic events, and vasospasm or dissection due to an eCLIPs microcatheter.TheuniquedesignoftheeCLIPsrequirestheinsertionofacatheterorguidewireintobothdaughterbranches. Therefore, it is important to consider vessel structure, including the diameter of the branch and the angle at which it forms with the parent artery.…”
Section: Other Stenting Techniquesmentioning
confidence: 99%